Investigation of the influence of liquid surface films on O3 and PAN deposition to plant leaves coated with organic/inorganic solution. Issue 23 (13th December 2016) - Sun, Shang; Moravek, Alexander; Trebs, Ivonne; Kesselmeier, Jürgen; Sörgel, Matthias
Abstract: This study investigates the influence of leaf surface water films on the deposition of ozone (O3 ) and peroxyacetyl nitrate (PAN) under controlled laboratory conditions. A twin‐cuvette system was used to simulate environmental variables. We observed a clear correlation between the O3 deposition on plants ( Quercus ilex ) and the relative humidity (RH) under both light and dark conditions. During the light period the observed increase of the O3 deposition was mainly attributed to the opening of leaf stomata, while during the absence of light the liquid surface films were the reason for O3 deposition. This finding was supported by experimentally induced stomatal closure by the infiltration of abscisic acid. In the case of PAN, no relationship with RH was found during the dark period, which indicates that the nonstomatal deposition of PAN is not affected by the liquid surface films. Consequently, the ratio of the O3 and PAN deposition velocities is not constant when relative humidity changes, which is in contrast to assumptions made in many models. The flux partitioning ratio between nonstomatal and stomatal depositions as well as between nonstomatal and total depositions was found to be R nsto/sto  = 0.21–0.40, R nsto/tot  = 0.18–0.30 for O3 and R nsto/sto  = 0.26–0.29, R nsto/tot  = 0.21–0.23 for PAN. Furthermore, we demonstrate that the formation of the liquid surface film on leaves and the nonstomatal O3 deposition are depending on the chemical composition of the particles deposited on the leaf cuticles as proposed previously. Key Points: Liquid water films enhance ozone deposition to plant leaves The deposition of peroxy acetyl nitrate (PAN) is not affected by liquid water films The deposition flux is depending on the chemical composition of the leave surface film